Seismic behaviour of traditional half-timbered walls : cyclic tests and strengthening solutions - Poletti, Elisa (2012)
Half-timbered buildings represent an important historical heritage in many countries. They are diffused in various regions for different reasons, such as availability of materials, to lighten a structure, their low cost, the strength they offer and as a construction element able to resist seismic actions. This latter issue is the research topic analysed here, as half-timbered buildings have been specifically used in reconstruction plans as earthquake-resistant buildings in many countries, such as Portugal, Italy, and Greece. All these buildings were characterized by an internal timber skeleton constituted of vertical and horizontal elements and braced with diagonal elements (St. Andrew’s crosses). This structure aimed at improving the global stability of masonry buildings, enhancing their capacity to dissipate energy during earthquakes. The aim of this paper is to study the behaviour under cyclic loading of such half-timbered walls, with typical connections, materials and geometries encountered in existing buildings. In general, half-timbered walls act as shear walls and confer to the masonry structure a better seismic resistance than that provided by a traditional masonry wall. Cyclic test were performed on traditional walls and their behaviour was studied in terms of ultimate capacity, deformability, energy dissipation and stiffness. Subsequently, the tested walls were retrofitted with traditional techniques in order to understand the influence of the reinforcement and to estimate its effectiveness, or lack thereof.